2013
DOI: 10.2166/wst.2013.686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the As Samra wastewater treatment plant upgrade on the water quality (COD, electrical conductivity, TP, TN) of the Zarqa River

Abstract: The impact of the As Samra wastewater treatment plant upgrade on the quality of the Zarqa River (ZR) water was investigated. Time series data that extend from October 2005 until December 2009 obtained by a state-of-the-art telemetric monitoring system were analyzed at two monitoring stations located 4 to 5 km downstream of the As Samra effluent confluence with the Zarqa River and about 25 km further downstream. Time series data that represent the ZR water quality before and after the As Samra upgrade were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…COD values were 10 and 17 mg/l for the treated wastewater and groundwater, respectively. A similar situation was recognized in Jordan, where two monitoring wastewater treatment stations were studied for their water quality before and after stations upgrade (Al-Omari et al, 2013). On the other hand, biochemical oxygen demand (BOD) of Bani-Malik WWTP was 2.8 mg/l and the suspended solids (SS) were 130.5 mg/l.…”
Section: Resultsmentioning
confidence: 66%
“…COD values were 10 and 17 mg/l for the treated wastewater and groundwater, respectively. A similar situation was recognized in Jordan, where two monitoring wastewater treatment stations were studied for their water quality before and after stations upgrade (Al-Omari et al, 2013). On the other hand, biochemical oxygen demand (BOD) of Bani-Malik WWTP was 2.8 mg/l and the suspended solids (SS) were 130.5 mg/l.…”
Section: Resultsmentioning
confidence: 66%
“…Hence, there are no xenoestrogen threats from the water treatment plant. However, it has been reported that As-Samra treatment plant needs further improvements [ 100 ]. More about the concentration of estrogenic activity in the surface water is found in a review [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the water quality permanganate index (COD Mn ), ammonia nitrogen, TP, and TN, 500 mL of the water sample was collected at ~0.5 m below the water surface of the lake using a 5 L water sampler. Then, 1 mL of sulfuric acid (concentration: 1.84 g/mL) was added to fix it [20][21][22][23], followed by storage at low temperatures, and the sample was finally taken back to the laboratory for further determination.…”
Section: Water Quality Sampling Treatment and Experimentationmentioning
confidence: 99%